2016
DOI: 10.1016/j.ijpara.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Assessing myxozoan presence and diversity using environmental DNA

Abstract: Amplicon sequencing on a High Throughput Sequencing (HTS) platform (custom barcoding) was used to detect and characterise myxosporean communities in environmental DNA samples from marine and freshwater environments and in faeces of animals that may serve as hosts or whose prey may host myxosporean infections. A diversity of myxozoans in filtered water samples and in faeces of piscivores (otters and great cormorants) was detected, demonstrating the suitability of lineage specific amplicons for characterising ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 41 publications
(30 reference statements)
4
43
0
Order By: Relevance
“…Although parasitism has originated seven times independently in the Cnidaria (Weinstein & Kuris, ; considering a common origin for Myxozoa and P. hydriforme ), myxozoans are the only group that is parasitic throughout their whole life cycle, has developed an indirect life cycle and shows extremely successful diversification, currently constituting about one‐fifth of all cnidarian taxa (Zhang, ), with diversity estimates from eDNA accounting for an approx. thirteen times higher number than presently known (Hartikainen et al., ). We showed that myxozoans diversified massively predominantly after the acquisition of their second hosts, fishes, approx.…”
Section: Discussionmentioning
confidence: 77%
“…Although parasitism has originated seven times independently in the Cnidaria (Weinstein & Kuris, ; considering a common origin for Myxozoa and P. hydriforme ), myxozoans are the only group that is parasitic throughout their whole life cycle, has developed an indirect life cycle and shows extremely successful diversification, currently constituting about one‐fifth of all cnidarian taxa (Zhang, ), with diversity estimates from eDNA accounting for an approx. thirteen times higher number than presently known (Hartikainen et al., ). We showed that myxozoans diversified massively predominantly after the acquisition of their second hosts, fishes, approx.…”
Section: Discussionmentioning
confidence: 77%
“…These include both ectoparasites like Amyloodinium ocellatum Brown, 1931 [ 38 ], Chilodonella hexasticha Kiernik, 1909 [ 39 ] or Neobenedenia girellae Hargis, 1955 [ 40 ] and endoparasites such as Opisthorchis viverrini Poirier, 1886 [ 41 ], Ichthyophonus spp . [ 42 ] and myxozoans [ 43 , 44 ]. Unlike traditional monitoring, there is no need to kill large numbers of fish or to carry out time-consuming manual examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Littoral marine, brackish water and sediment samples were collected from Newton’s Cove and the Fleet Lagoon (Weymouth, SW England) by Hartikainen et al (2014) , together with agricultural soil samples ( Gosling et al, 2014 ), and freshwater samples from the River Avon (Bickton) and California Lake (Berkshire) ( Hartikainen et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%